Investigating theatre devising for collective dialogue between deaf and hearing performers: a casestudy of From the Hip: Khulumakahle (FTH:K) - Mabena, Simangele (My University, 2010)
ABSTRACT It is generally presumed that the Deaf community is identified by their “health-related inability” (Shapiro, 1999:87) modelled on a medical paradigm. This paradigm negatively affects the Deaf community, exacerbating the barriers the Deaf encounter in identifying as an independent cultural and linguistic minority in the greater South African society. This paper seeks to investigate the use of theatre devices in facilitating collective dialogue between hearing and Deaf performers. Drawing on the literature which establishes sign language as linguistically sophisticated and therefore on a par with spoken and written language, this paper identifies a shared language as a possible unifying element between the two communities. It further investigates the structures present in creating meaning in theatre and their correlation with the languages of the hearing and Deaf. Using a case study of a Deaf/hearing integrated theatre company, From the Hip: Khulumakahle (FTH:K), the paper critiques Ladd’s (2003) notion of ‘Integrated Theatre’ in the theatre devising process of FTH:K. The research involved a qualitative case study methodology of participant observations, extensive field notes and individual interviews with the Deaf and hearing performers. The results of the study indicate that Deaf and hearing performers communicate using South African Sign Language1t to speak amongst each other. FTH:K has also begun exploring the gestural and imagistic language used between performers to collectively devise theatre amongst Deaf and hearing performers, as it does not privilege one language over another. Another key finding from the study was FTH:K’s concepts of ‘family’ and ‘playing’ as key elements in the theatre devising process. The performers in the theatre devising process often adhere to familial roles in creating their own form of integrated theatre. This study therefore critiques Ladd’s generalised statement about Integrated Theatre but also seeks to interrogate the influence of familial power relations in FTH:K’s theatre devising process. 1 From this point onwards I will refer to South African Sign Language as SASL